Management of Infrastructure in Improving the Quality of Vocational High School Graduates - Aisah, Iis; Achmad, Achmadi; Khoeriah, N. Dede; Sudrajat, Adjat (AGUSPATI Research Institute, 2021)
The dissertation with the title